Autoantibodies and cancer among asbestos-exposed cohorts in Western Australia. Issue 11 (3rd June 2021) - Carey, Renee N; Pfau, Jean C; Fritzler, Marvin J; Creaney, Jenette; de Klerk, Nicholas; W (Bill) Musk, Arthur; Franklin, Peter; Sodhi-Berry, Nita; Brims, Fraser; Reid, Alison
ABSTRACT: Asbestos exposure is associated with many adverse health conditions including malignant mesothelioma and lung cancer as well as production of autoantibodies. Autoantibodies may serve as biomarkers for asbestos exposure in patients with cancer, and autoimmune dysfunction has been linked to increased rates of various cancers. The aim of this study was to examine the hypothesis that autoantibodies are more frequent in asbestos-exposed individuals with either lung cancer or mesothelioma than those without these conditions. Asbestos-exposed individuals from Western Australia who had lung cancer (n = 24), malignant mesothelioma (n = 24), or no malignancy (n = 51) were tested for antinuclear autoantibodies (ANA) using indirect immunofluorescence and specific extractable nuclear autoantibodies (ENA) employing a multiplexed addressable laser bead immunoassay. Contrary to the hypothesis, data demonstrated that individuals without malignancy were more likely to be positive for ANA compared to those with cancer. However, autoantibodies to histone and Ro-60 were found to be associated with lung cancer. These results support a possible predictive value for specific autoantibodies in the early detection of lung cancer and/or in our understanding of the role of autoimmune processes in cancer. However, further studies are needed to identify specific target antigens for the antibodies.